2021
DOI: 10.3389/fmed.2021.793040
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma-Derived Extracellular Vesicles Impair Normal Hematopoiesis by Acting on Hematopoietic Stem and Progenitor Cells

Abstract: Multiple myeloma (MM) is characterized by the abnormal proliferation of clonal plasma cells (PCs) in bone marrow (BM). MM-PCs progressively occupy and likely alter BM niches where reside hematopoietic stem and progenitor cells (HSPCs) whose viability, self-renewal, proliferation, commitment, and differentiation are essential for normal hematopoiesis. Extracellular vesicles (EVs) are particles released by normal and neoplastic cells, such as MM cells. They are important cell-to-cell communicators able to modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Of note, we think that AML-EV treatment induced specific effects on HSPCs. In fact, performing similar experiments in another neoplastic context, such as MM, we obtained different results in HSPC differentiation and related functions ( 19 ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Of note, we think that AML-EV treatment induced specific effects on HSPCs. In fact, performing similar experiments in another neoplastic context, such as MM, we obtained different results in HSPC differentiation and related functions ( 19 ).…”
Section: Discussionmentioning
confidence: 83%
“…Our hypothesis supported by literature data reporting that AML-EVs contain RNA, DNA and proteins involved in the pathobiology of AML and that their signaling induces change in the proliferative, angiogenic and migratory characteristics of stromal cells and HSPCs ( 13 ). Recently, we demonstrated that the transfer of specific miRNAs by multiple myeloma (MM)-EVs in HSPCs also occur in MM setting reporting their increased levels in HSPCs after 20 h of MM-EV treatment ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed for the first time that MM-derived EV can inhibit normal hematopoietic stem and progenitor cells and dysregulate hematopoiesis. These results suggest that MM-derived EV might have an important impact on stem cells ( 15 ). Furthermore, we and others have demonstrated that EV content in MM patients is different from healthy subjects, revealing its significance in the MM setting ( 16 19 ).…”
Section: Introductionmentioning
confidence: 85%